Feasibility randomized controlled trial of a self-guided online intervention to promote psychosocial adjustment to unmet parenthood goals - Rowbottom, B (2022)
Is it feasible to implement and evaluate an online self-guided psychosocial intervention for people with an unmet parenthood goal (UPG), aimed to improve well-being, in an online randomized controlled trial (RCT)?